2010
DOI: 10.1002/nau.20972
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular morphometry of the uterine ligaments and vaginal wall in women with pelvic organ prolapse

Abstract: Both total innervation of the anterior vaginal epithelium and uterine ligaments, and muscular percentage of the round ligament and vaginal wall were decreased in women with pelvic organ prolapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 31 publications
2
12
0
Order By: Relevance
“…Many other reports have published concordant results with the study by Boreham et al (Table 3) [27][28][29][30]. The fraction of smooth muscle in the muscularis of the anterior vaginal wall was significantly decreased in women with POP and there was no significant difference between primary and recurrent cases.…”
Section: Morphometric Analysis Of the Vaginal Wallsupporting
confidence: 78%
See 2 more Smart Citations
“…Many other reports have published concordant results with the study by Boreham et al (Table 3) [27][28][29][30]. The fraction of smooth muscle in the muscularis of the anterior vaginal wall was significantly decreased in women with POP and there was no significant difference between primary and recurrent cases.…”
Section: Morphometric Analysis Of the Vaginal Wallsupporting
confidence: 78%
“…By evaluating the anterior vaginal wall innervation using PGP 9.5, Inal et al observed a decreased number and diameter of the subepithelial nerve fibers in the anterior vaginal wall of women with anterior prolapse than in women with normal vaginal support [29]. Kaplan et al recently confirmed their findings by describing decreased neuronization in the vaginal wall in the POP group [30].…”
Section: Innervation Of the Vaginal Wallmentioning
confidence: 97%
See 1 more Smart Citation
“…Pelvic floor muscles, uterosacral ligaments and endopelvic fascia represent the anatomical support for female pelvic organs, and their histological modifications could play a crucial role in the pathophysiology of the disease Kaplan et al 2011;Vulic et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In , one of the coauthors of the article has an incorrect first name given in the byline. The correct name is Ebru Tastekin, not Tugba Tastekin.…”
mentioning
confidence: 99%